2022
DOI: 10.3390/pathogens11020167
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Human Brucellosis Based on Infection Rate and Vaccination Coverage of Sheep and Goats

Abstract: In this study, the vaccination coverage, serological sampling and infection rate of sheep and goats were evaluated as predictors for the modeling of human brucellosis in Greece. The human brucellosis disease frequency per local regional unit (RU) varied significantly (RR90) among consecutive years. The notification rate was higher (p < 0.001) in the RUs with implementation of vaccination in sheep and goats (vaccination zone—VZ) with a median of 1.4 (IQR 0.0–3.1) compared with the RUs of the eradication zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Human brucellosis remains a persistent public health problem in some MSs, especially in Greece where brucellosis is endemic in sheep and goats. A mean annual notification rate of 0.9/100,000 population was documented in humans in 2005–2020 (Dougas et al., 2022 ; Kefaloudi et al., 2022 ). Since the EU‐level brucellosis surveillance started in 2007, Greece has reported a notification rate about 10 times higher than the EU average.…”
Section: Discussionmentioning
confidence: 99%
“…Human brucellosis remains a persistent public health problem in some MSs, especially in Greece where brucellosis is endemic in sheep and goats. A mean annual notification rate of 0.9/100,000 population was documented in humans in 2005–2020 (Dougas et al., 2022 ; Kefaloudi et al., 2022 ). Since the EU‐level brucellosis surveillance started in 2007, Greece has reported a notification rate about 10 times higher than the EU average.…”
Section: Discussionmentioning
confidence: 99%
“…were detected in <1% of people sampled [ 20 ]. With regard to animal infections, recent findings have indicated that the rate of new infected farms in the vaccination zone was significantly higher than in areas where eradication is carried out: 9 per regional unit (interquartile range: 2–23) versus 0 per regional unit (interquartile range: 0–2), respectively [ 26 ]. In 2016, the proportion of small ruminant farms with seropositive animals in three regions of the continental part (vaccination area) of the country was reported to be 4.6% overall (9.9% in Thessaly [ 27 ], 6.9% in Western Macedonia [ 28 ] and 1.8% in Peloponnese [ 29 ]), whilst in Crete no cases of the infection were recorded [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis is a serious and often neglected zoonosis caused by Brucella infection through contacting the contaminated animal and its products or air dusts . Livestock such as cattle, goats, sheep, camels, and pigs is the most common intermediate hosts of Brucellae , and humans, as the ultimate host, get sick through direct or indirect contact with infected animals or eating contaminated animal products . Around the world, 500,000 people are diagnosed with Brucella infection every year .…”
Section: Introductionmentioning
confidence: 99%